Mekanisme Ganti Kerugian Dalam Proses Praperadilan dan Peradilan : Tinjauan Hukum dan Praktik - Noor Ihsan, Reza; Fitrya Primadhany, Erry; Angraeni, Novita (Program Studi Hukum Universitas Pamulang, 2024)
The mechanism of compensation in the pretrial process aims to protect human rights and prevent abuse of power, as regulated by the Criminal Procedure Code (KUHAP) in Indonesia. The judiciary grants the accused the right to evaluate the validity of their arrest, detention, and the suspension of investigation and prosecution. Parties harmed by unlawful actions of law enforcement can file claims for compensation in pretrial for both material and immaterial losses. A single judge leads the process, which must be concluded within seven days. Two types of compensation are outlined: restitution, which means restoring the victim's condition, and compensation, where the state or perpetrator pays for the losses suffered by the victim. Despite clear regulations, the implementation of the compensation mechanism often faces various issues, such as a lack of funds and complex procedures. Furthermore, victims' rights are hindered because the state does not allocate specific funds for compensation payments. This mechanism is crucial as it protects human rights and justice for those who experience legal violations. The aim of this research is to comprehensively study the practices of pretrial and compensation in its implementation in Indonesia.